2007
DOI: 10.1016/j.taap.2007.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Biological stress response terminology: Integrating the concepts of adaptive response and preconditioning stress within a hormetic dose–response framework

Abstract: a b s t r a c tInhaled aerosol dose models play critical roles in medicine, the regulation of air pollutants and basic research. The models fall into several categories: traditional, computational fluid dynamical (CFD), physiologically based pharmacokinetic (PBPK), empirical, semi-empirical, and "reference". Each type of model has its strengths and weaknesses, so multiple models are commonly used for practical applications. Aerosol dose models combine information on aerosol behavior and the anatomy and physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
502
1
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 657 publications
(535 citation statements)
references
References 31 publications
10
502
1
7
Order By: Relevance
“…Using a sensitive in vivo chromosomal inversion assay (pKZ1 mouse prostate model), they demonstrated for the first time an adaptive response when a low X-ray dose (0.01-1 mGy) was given several hours after a high dose (1,000 mGy). This type of adaptive response has been called radiation post exposure conditioning hormesis (Calabrese et al 2007). The adaptive responses in this study were of similar magnitude to the adaptive responses previously observed in the indicated test system when the low dose was given first.…”
Section: Low-dose Radiation Prevents Harm From High Dosesmentioning
confidence: 99%
“…Using a sensitive in vivo chromosomal inversion assay (pKZ1 mouse prostate model), they demonstrated for the first time an adaptive response when a low X-ray dose (0.01-1 mGy) was given several hours after a high dose (1,000 mGy). This type of adaptive response has been called radiation post exposure conditioning hormesis (Calabrese et al 2007). The adaptive responses in this study were of similar magnitude to the adaptive responses previously observed in the indicated test system when the low dose was given first.…”
Section: Low-dose Radiation Prevents Harm From High Dosesmentioning
confidence: 99%
“…The low dose growth stimulation phenomenon of herbicides is known as herbicide hormesis (Calabrese et al, 2007). Growth stimulation due to low doses of different herbicides has been shown in several crop species both in controlled and in the field conditions (Davies et al, 2003;Duke et al, 2006;Cedergreen et al, 2007;Velini et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Stress is a signal indicating a potential or perceived threat (Calabrese et al, 2007;Joëls and Baram, 2009;Ulrich-Lai and Herman, 2009;McEwen and Gianaros, 2011). Stress is ubiquitous and has high biological significance because it enables rapid, delayed, and often enduring adaptive processes to changing circumstances (Calabrese et al, 2007;Joëls and Baram, 2009;McEwen and Gianaros, 2011).…”
mentioning
confidence: 99%
“…Stress is ubiquitous and has high biological significance because it enables rapid, delayed, and often enduring adaptive processes to changing circumstances (Calabrese et al, 2007;Joëls and Baram, 2009;McEwen and Gianaros, 2011). Accordingly, the central nervous system is equipped with several sensing mechanisms to identify stress, as well as processes to respond to stressful signals and be modified by them.…”
mentioning
confidence: 99%